Significant Roles of Children’s Literature In Efl - Ressy Novasyari (Global Expert: Jurnal Bahasa dan Sastra, 2019)
ABSTRACTThis article describes about the concept of children’s literature, the genre and the role of children’s literature in teaching English as a foreign language. In Indonesia, English as a foreign language because Indonesian use Bahasa Indonesia for communication.Children’s literature is a kind of literary texts such as picture story books, fable, novel, short stories etc in order to make students interested in reading especially for English as a foreign language. Sometimes they feel bored and lazy to learn English because they think  that it is a  difficult subject therefore, English teacher in Indonesia usually teaches the students with language combination between Indonesia and English in teaching and learning  pocess in order to make their students understand what they learn. Not only that, teachers always use textbook as material in teaching and learning process without introducing  new material like literature text and usually the use of teacher-centered strategy in classroom without involving students. One  solution  for solving this problem is introducing literature in teaching and learning process. Motivating students to learn English Literature is one of the best approach for teacher in teaching of English language skills (reading, writing, speaking and listening) because it can make students enhance their knowledge from story that they read in literary text.Keywords : Childrens’ literature, genre and role of children’s literatureABSTRAKArtikel ini akan menjelaskan tentang konsep sastra anak-anak, macam-macam dan peran sastra terhadap anak-anak dalam mengajar bahasa Inggris sebagai bahasa asing.Di Indonesia, Bahasa Inggris sebagai bahasa asing karena orang Indonesia menggunakan bahasa Indonesia untuk berkomunikasi.Sastra anak-anak adalah jenis teks sastra seperti buku cerita bergambar, dongeng, novel, cerita pendek dll supaya siswa tertarik membaca terutama untuk bahasa Inggris sebagai bahasa asing. Terkadang mereka merasa bosan dan malas belajar bahasa Inggris karena mereka pikir itu adalah pelajaran yang sulit oleh karena itu guru pelajaran bahasa Inggris di Indonesia biasanya mengajar siswa dengan menggunakan bahasa campuran antara bahasa Indonesia dan bahsa Inggris di proses belajar mengajar supaya siswa mengerti apa yang mereka pelajari. Tidak hanya itu, guru selalu menggunakan buku paket sebagai bahan ajar di proses belajar mengajar tanpa mengenalkan bahan ajar baru seperti teks sastra dan biasanya menggunakan strategi yang berpusat pada guru tanpa melibatkan siswa. Salah satu solusi untuk mengatasi masalah ini adalah memperkenalkan sastra dalam proses belajar mengajar. Memotivasi siswa untuk belajar Sastra Inggris adalah salah satu pendekatan terbaik untuk guru dalam mengajar keterampilan bahasa Inggris (membaca, menulis, berbicara dan mendengarkan) karena itu dapat membuat siswa meningkatkan pengetahuan mereka dari cerita yang mereka baca dalam teks sastra.Kata kunci : Sastra Anak- anak, macam sastra dan peran sastra anak- anak